Vitamin D and adolescent health - Faustino R Pérez-López; Gonzalo Pérez-Roncero; María T López-Baena (Dove Medical Press, 2010)
Faustino R Pérez-López, Gonzalo Pérez-Roncero, María T López-BaenaGrupo de Investigación sobre Salud de la Mujer en Aragón (GRISAMAR), Universidad de Zaragoza, Hospital Clínico Zaragoza, SpainAbstract: Vitamin D is a hormone sequentially produced at different body sites, and which plays a significant role in human health, particularly bone health. However, other roles are emerging. When the serum concentration of vitamin D is very low, the risk of rickets, osteomalacia and osteoporosis is increased. In children and adolescents there is a high prevalence of low vitamin D status, especially in females and during the winter–the prevalence being lower than during the summer. Although there is no unanimous agreement over the minimum values necessary for good health, serum 25-hydroxyvitamin D [25(OH)D] levels below 20 ng/mL may be regarded as a vitamin D-deficient condition, and levels between 20–30 ng/mL may be the range of vitamin D insufficiency. Mild low levels have been associated with bone mass accrual alterations in children and adolescents, diminished muscle strength, negative cardiovascular outcomes, insulin resistance and obesity, and neurological disorders. Effective preventive strategies are needed to guarantee adequate vitamin D levels throughout childhood and adolescence, taking into account the geographical setting, season of the year, the level of environmental pollution, skin characteristics, eating habits and body weight, with a view to securing optimum health during these phases, and the prevention of complications in adulthood. There needs to be a renewed appreciation of the beneficial effect of moderate sunlight for providing all humans with the vitamin D needed for ensuring good health. Prolonged sun exposure is not advised, however, due to the risk of skin cancer. In addition, a balanced diet is indicated, since vitamin D-rich foods are better assimilated than supplements. When such conditions cannot be met, then the supplementation of 400 IU/day of vitamin D is advised in children and adolescents–though correcting vitamin D insufficiency or deficiency may require 1000 IU/day or more. High-dose calcifediol depots are an alternative for guaranteeing treatment adherence and in patients with liver disease.Keywords: Vitamin D, rickets, osteomalacia, osteoporosis supplements, balanced diet